A representação do diverso no cinema de animação - Felipe de Castro Ramalho (2020)
One of the main agendas of the LGBT community is to combat the stereotypical representation in media that can vilify and mischaracterize their individuals and struggles. From this, we question these characterizations in the Hollywood animated movies. The animated films, quite often considered to be a product exclusively for children, it does not address directly the sexualities which differ of heteronormativity. For this reason, we named "diverse" the characters that flees the norms of heterosexuality standards in order to map, analyze, quantify and qualify these representations. At first moment, the concepts of the theorist Stuart hall on representational practices able of producing ideologies, speeches and signs are used in the animated film and associated with the anthropomorphism, which we believe to be a cloaked way to represent the various characters. Thereafter, we characterized the diverse and the reasons for the choice of the term to propose and debate on films as instance able to subscribe to the rules of gender and how the animated film acts as a media able to propose a specific cultural pedagogy. Therefore, from the principle of similarity and difference proposed by Hall, we map the diverse characters present in the history of animated film of the major American studios: Disney, Pixar, and DreamWorks. After these processes we evaluate and qualify from the tables developed for mapping, the purpose of the diverse representations on characters present in animated movies.